Challenges of E-marketing in India - Sharma, P; Rani, A (International Journal of Computer Sciences and Engineering, 2025)
The aim of this study is to explore the challenges of e-marketing in India. Electronic commerce is a revolution that many industry and academic observer believe will transform the conduct and structure of business. This range of interesting developments and innovations that are occurring in information goods, firm business processes, electronic marketplaces, and emerging industries in the economy further increase the impetus to broaden efforts in research on electronic commerce. Shopping is one of the essential part of our daily life. Internet has brought nearly the entire world just a click away from us. The retail industry canvass has been repainted by internet and the rules of the game in retailing are fast changing. The western culture has affected each and every aspect of our Indian society. The life is becoming fast not only in the metros but also in the normal cities. The number of nuclear families is increasing and both husband and wife are working, as they have less time to go to the market for purchasing every now and then. Some other reasons like these, say shortage of time, traffic jams, late working hours, versatility of plastic money and above all the improved their service and are providing more and more convenience to the customers. From advance payment options they moved on to payment on delivery